2014
DOI: 10.1186/s12870-014-0276-5
|View full text |Cite
|
Sign up to set email alerts
|

Populus tremula (European aspen) shows no evidence of sexual dimorphism

Abstract: BackgroundEvolutionary theory suggests that males and females may evolve sexually dimorphic phenotypic and biochemical traits concordant with each sex having different optimal strategies of resource investment to maximise reproductive success and fitness. Such sexual dimorphism would result in sex biased gene expression patterns in non-floral organs for autosomal genes associated with the control and development of such phenotypic traits.ResultsWe examined morphological, biochemical and herbivory traits to tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 71 publications
7
37
0
Order By: Relevance
“…Equivalent to studies on somatic and reproductive tissues in animal systems (Mank, ; Pointer et al., ; Yang et al, ), we found that the reproductive tissue was far more transcriptionally dimorphic than the vegetative tissue (Figures and ). Additionally, in plant species in particular, very few studies have been able to identify any significant sex‐biased genes in nonreproductive tissues (Robinson et al., ; Zemp, Minder, & Widmer, ; Zluvova et al., ). We also found that, in catkin, male‐biased genes were expressed at significantly higher levels and had a higher magnitude of sex‐bias than female‐biased genes (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Equivalent to studies on somatic and reproductive tissues in animal systems (Mank, ; Pointer et al., ; Yang et al, ), we found that the reproductive tissue was far more transcriptionally dimorphic than the vegetative tissue (Figures and ). Additionally, in plant species in particular, very few studies have been able to identify any significant sex‐biased genes in nonreproductive tissues (Robinson et al., ; Zemp, Minder, & Widmer, ; Zluvova et al., ). We also found that, in catkin, male‐biased genes were expressed at significantly higher levels and had a higher magnitude of sex‐bias than female‐biased genes (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to animals, where sexual dimorphism is more frequent, only a small percentage (~5%) of flowering plants are dioecious (Renner, ; Robinson et al., ), where individuals have exclusively male or female reproductive organs. The majority (~90%) of angiosperms are hermaphroditic (Ainsworth, ; Barrett & Hough, ), where flowers are bisexual, while another small fraction are monoecious, where separate flowers within the same plant carry different reproductive organs (Renner, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A consequence of these adaptations could be the appearance of a phenotypic, biochemical, and ecological dimorphism, resulted from the resource allocation specifi ed for each sex, creating a state of great application depending on the specifi c needs of each sex (ROBINSON et al, 2014). Height and diameter have been the phenotypic characteristics most used as indicators to analyze these changes related to sex, considering that the vegetative vigor is the result of a larger adaptive capacity (DUDLEY, 2006;PETZOLD et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is possible to perceive that the estimates of commercial biomass for male plants tended to be similar to the measured commercial biomass when compared to those of the female sex. This difference between sexes has been common in dioecious forestry species, and has been explained by the biological, biochemistry and phenotypic variation between sexes, resulting from the allocation of specific resources to supply each sex demands (ROBINSON et al, 2014;RAKOCEVIC et al, 2007;2009).…”
Section: Figurementioning
confidence: 99%